The acquisition of Russian motion verbs by Italian-speaking students in light of new linguodidactic concepts - Piccolo, Federico (Vilnius University Open Series, 2024)
The research presented in the article aims to identify linguodidactic principles that would help to shape the forma mentis of Italian-speaking students studying the Russian language, and assist them in the process of learning and acquiring motion verbs while avoiding errors due to interference between L1 (Italian) and FL (Russian) in encoding deictic information. The study raises several important questions: Why do students make mistakes in using motion verbs despite their high level of proficiency in Russian? What innovative approaches can facilitate the learning of Russian motion verbs?
Keywords: motion verbs; contrastive analysis in linguodidactics; didactics of the Russian language